Governance for development in Africa : solving collective action problems - Booth, David, 1945-; Cammack, Diana Rose, 1945- (London ; New York : Zed Books, 2013)
Drawing on in-depth empirical research spanning a number of countries in Africa, this path-breaking book controversially argues that externally imposed good-governance approaches make unrealistic assumptions about the choices leaders are able to make, while ignoring the potential for addressing causes rather than symptoms. It offers a comprehensive, critical examination of the institutional barriers to economic and social progress in Africa and makes a compelling plea for fresh policy thinking.
Introduction -- From 'good governance' to governance that works -- The country contexts -- Maternal health : why is Rwanda doing better than Malawi, Niger and Uganda? -- The politics of policy incoherence and provider indiscipline -- The space for local problem-solving and practical hybridity -- Conclusion -- Bibliography -- index.
Includes bibliographical references (pages 140-154) and index.
Print version record.
Keywords: 2000-2099; Public administration -- Africa; Economic assistance -- Africa; POLITICAL SCIENCE -- Government -- Executive Branch; Economic history